Development of vehicle lane changing model within u-turn facilities - Nemmang, Mohd Shafie (2017)
U-turning movements at roadway segments are channelized and aided with splitting islands in the middle so that drivers can be on their desired trajectories and the road segment are often accompanied with weaving, merging and diverging movement. The objectives are to determine the speed differences (Vd), reaction time (RT) and safe distance where from those parameters and their relationships, the statistical model was developed and used in estimating the safe distances to execute the lane changing within the U-turn facilities. The data were taken from the field which is video recording, picture and geometric design and was used to simulate the driving simulator like an actual environment while the driving simulator come out with the speed differences, reaction time and distance as a raw data. Result show that the mean value of reaction time (RT) of the driver in making the lane changing at the U-turn area is 2.5s where the distance to execute the lane changing is 16.467m from the merging vehicle. Through the relationship between the RT, Vd and distance of the subject vehicle within U-turn facilities, the findings from the statistical model has been developed with the equation [Safe distance = (13.448 + 1.410 RT – 0.075 Vd)]. The model was used to estimate the safe distance which is 15.00m within U-turn facilities. The result shown that the safe distance will increase when the driver slowing down their speed and increasing the reaction time. The research concluded that the speed difference and reaction time have a significant relationship in estimating the safe distance in executing the lane changing within U-turn facilities.